Seasonal variations for newly prescribed urate-lowering drugs for asymptomatic hyperuricemia and gout in Japan - Kurajoh, Masafumi; Akari, Seigo; Nakamura, Takashi; Ihara, Yasutaka; Imai, Takumi; Morioka, Tomoaki; Emoto, Masanori (Frontiers in Pharmacology, 2024)
Background: Urate-lowering drugs (ULDs) have been approved for treatment of asymptomatic hyperuricemia and gout in Japan. Although serum urate levels and rates of gout onset are known to have seasonal variations, no survey results regarding the seasonality of ULD prescriptions for asymptomatic hyperuricemia and gout have been reported. Methods: A large-scale database of medical claims in Japan filed between January 2019 and December 2022 was accessed. In addition to total size of the recorded population for each month examined, the numbers of patients every month with newly prescribed ULDs for asymptomatic hyperuricemia and gout were noted, based on the International Classification of Diseases, 10th Revision, codes E79.0 and M10. Results: The results identified 201,008 patients with newly prescribed ULDs (median age 49.0 years, male 95.6%). Of those, 64.0% were prescribed ULDs for asymptomatic hyperuricemia and 36.0% for gout. The proportion of new ULD prescriptions was seasonal, with that significantly (p<0.001) higher in summer (June-August) [risk ratio (RR) 1.322, 95% CI 1.218 to 1.436] and autumn (September-November) (RR 1.227, 95% CI 1.129 to 1.335) than in winter (December-February), whereas the proportion in spring (March-May) was not significantly different from winter. There was no significant difference after stratification by drug type (uric acid production inhibitor/uricosuric agent) or size of the medical institution, nor subgrouping by age or sex (p for interaction=0.739, 0.727, 0.886, and 0.978, respectively). On the other hand, the proportions of new ULD prescriptions for asymptomatic hyperuricemia were significantly lower and for gout significantly higher in spring than winter, while those were similar in summer and autumn for both groups (p for interaction<0.001). Conclusion: The present findings indicate that new prescriptions for ULDs to treat asymptomatic hyperuricemia or gout in Japan show seasonal differences, with higher rates noted in summer and autumn as compared to winter.